Ovarian Hyperstimulation Syndrome: A Simulation Case for Emergency Medicine Residents - Kathleen A. Wittels; Katherine Dickerson Mayes; Andrew Eyre (Association of American Medical Colleges, 2022)
Introduction Ovarian hyperstimulation syndrome (OHSS) is a complication of assisted reproductive technology (ART) for infertility. Given the potential for significant morbidity, it is important for emergency medicine (EM) residents to be able to recognize and initiate treatment for this disorder. Methods A high-fidelity human patient simulator was used, with availability of bedside ultrasound. PGY 1-4 EM residents participated in this case of a 28-year-old female patient undergoing treatment for infertility who presented to the emergency department with shortness of breath and near syncope. Workup revealed a diagnosis of OHSS. After the simulation, we surveyed residents on their knowledge of OHSS prior to participation in the simulation. We also asked about their confidence in caring for a patient with OHSS pre- and postsimulation based on a 5-point Likert scale. Results A total of 24 EM residents completed this simulation case. Prior to participating in the simulation experience, 62% of residents reported that they had heard of OHSS, and 17% of residents had previously managed a patient with OHSS. After participating in the simulation, residents' comfort with managing a patient with OHSS increased from 1.7 to 3.7 points (1 = not at all comfortable, 5 = extremely comfortable; p < .001). Discussion OHSS is a rare but important complication of ART that many EM residents have not treated in the clinical environment. As the presenting symptoms may mimic other diagnoses, obtaining a detailed history and utilizing bedside ultrasonography are essential to diagnosing and correctly treating these patients.